9/11 and the literature of terror - Randall, Martin (Edinburgh University Press, 2011)
Explores the fiction, poetry, theatre and cinema that have represented the 9/11 attacks Works by Martin Amis, Ian McEwan, Don DeLillo, Simon Armitage and Mohsin Hamid are discussed in relation to the specific problems of writing about such a visually spectacular 'event' that has had enormous global implications. Other chapters analyse initial responses to 9/11, the intriguing tensions between fiction and non-fiction, the challenge of describing traumatic history and the ways in which the terrorist attacks have been discussed culturally in the decade since September 11. Key Features Contributes to the growing literature on 9/11, presenting an over-view of some of the main texts that have represented the attacks and their aftermath Focus on Don DeLillo: adds to the literature surrounding this major American novelist Focus on Martin Amis: adds to the growing critical work on this much discussed British novelist and essayist Man on Wire: provides a critical analysis of this Oscar winning film regarding its oblique references to 9/11